Water Rights in Southeast Asia and India - Pink, Ross Michael. author. aut Link
IX, 253 p.
Keywords: This fascinating book examines the paramount human rights issue of our time: clean drinking water. Pollution, population surge, and climate change will deprive an estimated 2 billion citizens of this fundamental right by 2050. The author argues for the need to establish innovative, sustainable practices to safeguard this precious human right.